(untitled) (Journal of International Studies, 2020)
The crisis in Zimbabwe in the past decade has many dimensions. One of the underestimated dimensions is the impact of Western media reportage on the unfolding drama in the country. Biased reportage by some mainstream Western media channels on Zimbabwe has had a negative and damaging effect both on the Mugabe regime as well as the country’s economy. It has also highlighted the excesses of the Mugabe regime in its quest to ensure regime security. In response to these Western media blitz, the Mugabe regime has countered them by stifling media independence in the domestic arena in a calculated strategy aimed at cushioning itself from unfair and biased media attacks. While there is some truth in what is being reported about the Mugabe regime by the Western media, on balance, this paper argues that the role played by the Western media in the ensuing political crisis in Zimbabwe has done more harm than good. In a big way, the Western media has aggravated the political and socioeconomic crisis in Zimbabwe in the past decade.